AN ANALYSIS STUDENTS’ ABILITY IN TRANSLATING FROM INDONESIAN INTO ENGLISH AT ENGLISH STUDY PROGRAM OF BATURAJA UNIVERSITY - Fila Olivia; Nurhasanah Nurhasanah; Mila Arizah (Program Studi Pendidikan Bahasa Inggris - Fakultas Keguruan dan Ilmu Pendidikan - Universitas Baturaja, 2021)
The aim of this study was to find out the students’ ability in translating argumentative text from Indonesian into English at English Study Program of Baturaja University. In analyzing the data the writer used descriptive method. The population of this study was the English Study Program of Baturaja University in academic year 2020/2021 that consisted of 35 students. Based on pre-observation, most of the students at English Study Program of Baturaja University need to acquire translation ability. Because not all people know the meaning of English words, sentences or text, English students can be a tool to help people to communicate with others. Based on the sample was taken by using simple random sample and the writer put three categories on the sample. The categories are (1) go to a good hat store and buy a big top hat, (2) make one slip of paper for each individual in the population and place all of the slips in the hat, (3) make sure you used standard-sized slips of paper so that they will all be the same shape, size, and weight. The students percentage score in argumentative text test in 66,1 % in good level mastery. It meant that an analysis students’ ability in translating from Indonesian into English at English Study Program of Baturaja University is accurate.